(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the safety, oncological efficacy, and complication-reducing capability of video endoscopic inguinal lymphadenectomy with great saphenous vein preservation in patients with penile squamous cell carcinoma. Methods: A case series study was conducted on 38 patients who underwent video endoscopic inguinal lymphadenectomy with great saphenous vein preservation at Viet Duc University Hospital between March 2022 and March 2025. Evaluated parameters included perioperative outcomes, postoperative complications (graded by the Clavien-Dindo classification), disease-free survival, and inguinal recurrence-free survival. Survival analysis was performed using the Kaplan-Meier method and the log-rank test. Results: The study cohort comprised 38 patients with a mean age of 52.9 ± 11.1 years. The mean overall operative time was 136.1 ± 35.1 minutes. The mean inguinal lymph node yield was 16.9 ± 5.6 nodes. The flap-preserving technique was associated with excellent surgical outcomes, achieving a 0% rate of both surgical site infection and skin flap necrosis. The overall complication rate was 18.4%, with a postoperative seroma rate of 7.9%. Over a median follow-up of 29.5 months, the 2-year disease-free survival and inguinal recurrence-free survival rates were 89% and 97%, respectively. Correlation analysis using a 12-node cutoff revealed no significant differences in disease-free survival (p = 0.362) and inguinal recurrence-free survival (p = 0.637) between patients with < 12 nodes and those with ≥ 12 nodes during the follow-up period. Conclusions: Video endoscopic inguinal lymphadenectomy with great saphenous vein preservation is a safe, feasible, and oncologically highly effective procedure. This technique eliminates the risk of surgical site skin necrosis, significantly minimizes lower limb lymphedema, and ensures an optimal lymph node yield alongside durable local disease control.